Advances and Technologies in Building Construction and Structural Analysis - Kaboli, Alireza; Shirowzhan, Sara (IntechOpen, 2021)
This Edited Volume "Advances and Technologies in Building Construction and Structural Analysis" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of advances and technologies in building construction and structural analysis. The book comprises single chapters authored by various researchers and edited by an expert active in the alternative medicine research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on advances and technologies in building construction and structural analysis and opening new possible research paths for further novel developments.